TENZEL ROTATIONAL FLAP IN UPPER AND LOWER LID RECONSTRUCTION IN TERTIARY CARE HOSPITAL OF KARACHI PAKISTAN: A PROSPECTIVE INTERVENTIONAL STUDY - Ahmed, Fatima; Kamil, Zeeshan; Khan, Muhammad Tanweer Hasan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Reconstruction of the lids is a significant challenge for ocular plastic surgeons as it requires the greatest functional and cosmetic outcomes. This study aimed to share the experience of Tenzel rotational flap in upper and lower lid reconstruction of anterior lamella at a tertiary eye care hospital of Karachi, Pakistan. Methods: 10 patients with upper and lower eyelid defects over a period of 6 months were a part of this prospective interventional clinical study. The examination on the subject was performed at tertiary care hospital of Karachi, Pakistan after ethical approval. Pre and post operation evaluation LPS (Levator palpebrae superioris) action MRD-1 (Margin Reflex Distance-1) values central vertical Palpebral Fissure Height (PFH) were recorded. Data was entered and analyzed on SPSS version 23.0. Results: For the upper eyelid the preoperative measurements of MRD-1, LPS action, central palpebral aperture were -1.6±1.63 mm, 4.33±1.21 mm and 4.33±1.33 respectively. The postoperative measurements of these parameters were 3.83±0.25 mm, 13.16±1.17 mm and 10.83±0.68 mm respectively. For the lower eyelid the Mean±SD of MRD-1, LPS action, central palpebral aperture preoperatively was 3.62±0.25 mm, 12.75±0.50 mm and 10.75±0.95 mm respectively. Postoperative values of MRD-1, LPS action, central palpebral aperture before operation were 3.83±0.25 mm, 12.75±0.50 mm and 10.75±0.95 mm respectively. The mean incision length in the upper and lower eyelid was 8.50±0.83 and 9.50±0.91 respectively. Conclusion: Tenzel rotational flap not only helps to heal the upper and lower eyelids but also there is no further requirement of additional surgery for posterior lamella. The study concluded that this technique provides both cosmetically and functionally aesthetics outcomes.